China goes to sea maritime transformation in comparative historical perspective - Erickson, Andrew S.; Goldstein, Lyle; Lord, Carnes (Naval Institute Press, 2009)
China's turn toward the sea is evident in its stunning rise in global shipbuilding markets, its expanding merchant marine, its wide reach of offshore energy exploration, its growing fishing fleet, and its increasingly modern navy. This comprehensive assessment of China's potential as a genuine maritime power is both unbiased and apolitical. Unlike other works that view China in isolation, it places China in a larger world historical context. The authors, all authorities on their historical eras, examine cases of attempted transformation from continental to maritime power through the ages, from the Persian Empire to the Soviet Union, and determine the reasons for success or failure.